2008
DOI: 10.1002/ptr.2339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Red Ginseng extract on ultraviolet B‐irradiated skin change in C57BL mice

Abstract: Red Ginseng (the roots of Panax ginseng C.A. Meyer) is used clinically in China, Korea and Japan for various diseases, including atherosclerosis, hypertension and stress etc. Although Red Ginseng roots have traditionally been thought to have antiageing effects, the basis for this hearsay is unclear. This study examined the effects of Red Ginseng extract on ultraviolet B (UVB)-irradiated skin ageing in mice. Oral administration of Red Ginseng extract (20 or 60 mg/kg, twice daily) prevented UVB-irradiated skin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Recently, RG was studied for cosmetic applications and as a cosmeceutical ingredient. [13][14][15]41,42 Some researchers have studied the fermentation of RG as a way to improve its biological activity. 43,44 Bae et al 43 reported that orally administered RG extract did not significantly protect against ischemicareperfusion brain injury, whereas fermented RG did.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, RG was studied for cosmetic applications and as a cosmeceutical ingredient. [13][14][15]41,42 Some researchers have studied the fermentation of RG as a way to improve its biological activity. 43,44 Bae et al 43 reported that orally administered RG extract did not significantly protect against ischemicareperfusion brain injury, whereas fermented RG did.…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenosides can induce antioxidant enzymes, such as superoxide dismutase and catalase, which are important for maintaining cell viability. 11 Many previous studies have reported that P. ginseng has anti-wrinkle effects, 12 protects against ultraviolet radiation-induced skin aging, 13,14 and has anti-melanogenesis effects. 15 Furthermore, it was reported that ginseng has immunostimulating activity.…”
Section: Introduction Gmentioning
confidence: 99%
“…ginseng has been shown to possess a wide range of biological and pharmacological activities and is used as a general tonic in traditional oriental medicine to increase vitality, health, and longevity, especially in older persons. Previous research has reported that ginseng has several beneficial effects on human and animal skin [3][4][5][6][7]. Kim et al [36] reported that topical applications of total ginseng saponins (10 pg or 100 ng/mouse) and ginsenoside Rb1 (100 fg, 10 pg, or 1 ng/mouse) isolated from red ginseng significantly inhibited increases in skin thickness and wrinkle formation and reduced skin elasticity induced by long-term UVB irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…14 The phenylpropanoid component of cinnamic acid has also been reported to exhibit a tyrosinase inhibitory effect and depigmenting activity in UVB-induced hyperpigmentation of the brown guinea pig. Recently, oral supplementation of red ginseng extracts (20 or 60 mg=kg of body weight, twice daily) was shown to inhibit the clinical damages such as epidermal hyperplasia, pigmentation, and wrinkles in UVB-irradiated skin, 36 but little is known about the effect of ginseng extracts on epidermal hydration or facilitating ceramide accumulation in epidermis.…”
Section: Discussionmentioning
confidence: 99%